Nails: The Window to the Nose? Update on Yellow Nail Syndrome - Laura Vollono; Marco Adriano Chessa; Antonio Bruno; Michela Starace; Aurora Alessandrini; Bianca Maria Piraccini (Mattioli1885, 2020)
Background: Yellow nail syndrome is a rare condition characterized by typical nail alterations and variable presence of lymphedema and respiratory disease. The pathogenesis is still obscure, with most of the literature deriving from case reports and few investigations. The most reported respiratory conditions associated with yellow nail syndrome are pleural effusion and bronchiectasis, whereas association with rhinosinusitis is rarer. Objectives: To describe a case of yellow nail syndrome and to provide a literature review regarding this condition, discussing pathogenetic hypothesis, associated conditions, and therapeutic options. Patients/Methods: A 49-year-old man presented with arrested growth and alterations of his nails, without any history of previous trauma or inflammation but with a severe nasal septum deviation and a history of chronic rhinosinusitis. A diagnosis of yellow nail syndrome was made. Results: Six months after undergoing rhinoseptoplasty and treatment with oral vitamin E, the patient's nails were cured. Conclusions: This case emphasizes the role of the dermatologist in detecting systemic conditions. The correct diagnosis led to complete resolution of both nail alterations and associated respiratory condition.